COMPARATIVE ANALYSIS OF QUALITY OF LIFE AFTER THORACIC ENDOVASCULAR AORTIC REPAIR AND OPTIMAL MEDICAL THERAPY IN PATIENTS WITH UNCOMPLICATED TYPE B AORTIC DISSECTION - Anna Yu. Shkandala; Oleh V. Zelenchuk; Serhii M. Furkalo; Borys M. Todurov; Andrii V. Khokhlov; Nataliia O. Yashchenko; Serhii M. Sudakevych (Клінічна та профілактична медицина)
Introduction. Thoracic endovascular aortic repair (TEVAR) is considered a minimally invasive intervention, but the impact of this intervention on quality of life has not yet been fully evaluated.